The effects of using reflective journals on reflective practice behaviors in the nursing administration practicum among fourth-year nursing students - ๋Piriyasart, Jitlada; Pairoh, Hasanah; Che Hasan, Muhammad Kamil (Praboromarajchanok Institute (Under Ministry of Health, Thailand), 2025)
This study employed an explanatory sequential mixed-methods design, consisting of a quantitative quasi-experimental one-group posttest-only approach and qualitative research. The objective was to examine the effects of using reflective journals on reflective practice behaviors in the nursing administration practicum. The quantitative sample comprised 43 fourth-year nursing students, while the qualitative sample included 7 students. Research instruments consisted of reflective journals, a reflective behavior assessment form, and a focus group interview guide. Quantitative data were analyzed using descriptive statistics, and qualitative data were analyzed using content analysis. The results showed as follows. 1. After using reflective journals, students demonstrated reflective practice behaviors above the 75% criterion with statistical significance (p-value < .001). 2. Effective self-management during the nursing administration practicum was enhanced by the use of reflective journals, which supported students in preparation, leadership development, and professional nursing practice. In conclusion, as students’ reflective practice behaviors exceeded the specified benchmark, nursing faculties should consider incorporating reflective practice into nursing education. This approach has the potential to foster positive professional attitudes, critical thinking, and leadership skills among nursing students.